2006
DOI: 10.1242/jcs.03033
|View full text |Cite
|
Sign up to set email alerts
|

Specific modulation of apoptosis and Bcl-xL phosphorylation in yeast by distinct mammalian protein kinase C isoforms

Abstract: Mammalian protein kinase C (PKC) isoforms have been subject of particular attention because of their ability to modulate apoptotic proteins. However, the roles played by each PKC isoform in apoptosis are still unclear. Here, expression of individual mammalian PKC isoforms in Saccharomyces cerevisiae is used as a new approach to study the role of each isoform in apoptosis. The four isoforms tested, excepting PKC-δ, stimulate S. cerevisiae acetic-acid-induced apoptosis essentially through a mitochondrial ROS-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
4
46
1
Order By: Relevance
“…7A and B), decreased  m ( Fig. 8A and B) and increased mitochondrial fragmentation ( It was showed that human Bcl-xL is also a mitochondrial anti-apoptotic protein in yeast, inhibiting yeast apoptosis induced by stress stimuli such as hydrogen peroxide, menadione [27] and acetic acid [17]. Moreover, a previous work performed by our group…”
Section: Coleon U-induced Growth Inhibition In Yeast Expressing Npkc-mentioning
confidence: 73%
See 4 more Smart Citations
“…7A and B), decreased  m ( Fig. 8A and B) and increased mitochondrial fragmentation ( It was showed that human Bcl-xL is also a mitochondrial anti-apoptotic protein in yeast, inhibiting yeast apoptosis induced by stress stimuli such as hydrogen peroxide, menadione [27] and acetic acid [17]. Moreover, a previous work performed by our group…”
Section: Coleon U-induced Growth Inhibition In Yeast Expressing Npkc-mentioning
confidence: 73%
“…Yeast expression of a mammalian PKC isoform and/or human Bcl-xL was previously confirmed by Western blot analysis [17,19].…”
Section: Plasmidsmentioning
confidence: 92%
See 3 more Smart Citations